88 Vitamin D deficiency in children with cancer – prevalence and screening. (15th December 2021) - Rossetto, Giulia; Renshaw, Gemma; Camacho, Angela; Gardiner, Breeana
Abstract : Background: Children with cancer are at high risk of vitamin D (vitD) deficiency and insufficiency. Following results from previous audit, a protocol was introduced at GOSH in 2018 to ensure all children with malignancy had vitD levels screened. Aim: To audit adherence to vitD screening protocol for children with cancer at GOSH and determine prevalence rates of vitD deficiency. Methods: VitD status (25-hydroxy vitamin D (25(OH)D) concentrations) of children with malignancy admitted to GOSH as inpatients/outpatients on six randomly selected days over 2020 was reviewed. Patients with vitD test results completed after April 2019 were included, due to ease of access with implementation of electronic medical records. Per national guidelines, serum VitD 25–50 nmol/L insufficient and <25nmol/L deficient. Results: Patients included n=140 (haematology n=76; oncology n=64); 58% (n=81) had vitD levels tested within 2 weeks of diagnosis; 67% (n=51 of 76) of patients with haematological malignancy were more likely to get tested at diagnosis compared to oncology (47%;(n=30 of 64)). Overall, 93% (n=131) had vitD tested at some point during their treatment compared to 57% in the previous audit. Of those(n=131), 20% (n=26) were insufficient and 8% (n=11) were deficient. Haematology had higher rates of deficiency (n=7;18%) than oncology (n=4;11%). Conclusion: This audit shows that although there have been improvements with the implementation of a hospital protocol, there is an ongoing need to ensure adherence to baseline vitD screening amongst children with malignancy at GOSH. It also shows that VitD deficiency is prevalent in children with malignancy, particularly amongst haematological malignancies, significantly higher than the general paediatric population (13%). Further work is needed to ensure standardised screening occurs and that appropriate treatment/monitoring commence promptly.